COMMUNICATION STRATEGY USED IN THE INTERACTION BETWEEN LOCAL GUIDES AND FOREIGN TOURISTS WHEN GUIDING IN MUSEUM KESEJARAHAN JAKARTA - Sri Arfani; Rini Martiwi; Hepi Andes (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2021)
This research was conducted to determine the communication strategy used by the local guide when guiding foreigners in museum kesejarahan Jakarta, especially the types of strategy in communication and the function of each strategy for the local guide to solving their problem in the museum. Communication strategy is the important thing that the guide needed to build a good conversation with the foreigners' visitor there. The objective of this study is to find out the most dominant type of strategy in communication and the functions of each strategy when the guide faced the problem when guiding, the writer used the descriptive qualitative method. The data collection was done by collecting the data from observation and the conversation problem with each foreign tourist. Primary data collected from direct field observations and interviews. The writer analyzes some conversations that can be shown as the problem faced by the tour guide. This research used theory by Celce-Murcia et al’s (1995) model of communication strategies is considered as the most complete and detailed. The writer divided communication strategies into five main categories. They are avoidance, achievement, stalling, self-monitoring strategies, and interactional strategies. Results showed that there were 5 types of communication strategy and The dominant of those theories was an interaction strategy. Problems that faced by the local guide are different culture, limited vocabulary, shyness, difficult accent, too attached to the modules being thought